DEMOGRAPHIC DETERMINANTS OF LABOUR MARKET PARTICIPATION IN NIGERIA - Ikwumezie, Aham; Callistus; Adaeze Maryann, Agu (International Journal of Multidisciplinary Reseach, 2025)
This research investigated demographic determinants of labour market participation in Nigeria. The specific objectives were to investigate the effects of age distribution, marital status, gender on labour market participation in Nigeria. Also, the study sought to determine the extent to which socio-economic factors (income level, education, occupation, size of household and geographic location) affects labour market participation in Nigeria. Data were drawn randomly from residents of five States in South East Nigeria using multi-stage sampling technique. The sample size was 363 drawn from a population of 14,322,000 residents of South East Nigeria. The data were coded in SPSS software and analyzed using multiple regression technique. The findings revealed that age and marital status significantly increased labour market participation in Nigeria while gender had decreasing effect on labour market participation in Nigeria. Education, income level and geographic location were the significant socio-economic determinants of labour market participation in Nigeria. While occupation increased labour market participation though not significantly, household size decreased labour market participation. The study concluded that labour market participation in Nigeria is primarily driven by socio-economic factors such as age distribution, marital status, education, income level, and geographic location. There was no clear evidence of gender-based disparities in labour market participation. The study recommended that Government should create policies that will address the disparities between urban and rural areas by improving infrastructure as well as encourage women participation in labour market.